PANCHAYATI RAJ INSTITUTIONS AND RURAL DEVELOPMENT: A STUDY ON RESPONSIBLE TOURISM INITIATIVE IN KUMARAKOM GRAMA PANCHAYATH - Anand Jayakrishnan K.
Despite being a consumerist state, Kerala was able to maintain high living standards matching those of highly developed nations, owing to its huge foreign remittances and human development. More than four decades have passed since the conception of ‘Kerala model of development’ and the earlier euphoria surrounding the model no longer exists as serious questions regarding its sustainability were raised in 1990s. Almost in the same decade, the idea of ‘New Kerala Model’ was mooted in academic circles. This new model, which promised to integrate sustainable development goals into policy making, was essentially rooted in the concept of decentralisation. However, over the years, Panchayati Raj Institutions (PRIs) have been vehemently criticised for their failure to take into account longterm aspirations of the locality and to implement projects without meaningful forward and backward linkages. It was almost in the same era that Kerala recognised the potential of tourism as an important income generator. The present paper reflects upon how problems associated with PRIs can be solved to an extent if we can effectively incorporate tourism as an alternate revenue source, through a study on responsible tourism initiative in Kumarakom Grama Panchayath. The aim of the present paper is to make an in-depth study regarding the role of tourism as an alternate revenue source for PRIs in Kerala. The two main objectives of the paper are (i) to trace the history of PRIs in Kerala and analyse the challenges faced by them during the post-liberalisation era (ii) to examine how tourism can be effectively used to overcome the challenges faced by decentralisation in Kerala through a case study in Kumarakom Grama panchayath. The paper employs descriptive and analytical methods to dissect facts and frameworks and to reach at outcomes.